Prelacrimal Approach to Maxillary Sinus Pathology. Issue 3 (May 2023) - Seresirikachorn, Kachorn; Kondo, Mickey; Png, Lu Hui; Kalish, Larry; Campbell, Raewyn G.; Alvarado, Raquel; Harvey, Richard J.
Background: Access to the anterior, lateral, inferior, and inferomedial maxillary sinus has been a limitation of the middle meatal antrostomy. Expanded techniques such as the modified medial maxillectomy provide access to many of these areas but require remucosalization, and crusting can occur during the recovery phase. The prelacrimal approach (PLA) offers direct 0° endoscope access to these areas. Additionally, PLA can preserve the nasolacrimal duct and mucosal coverage. Objectives: We describe the current surgical technique and outcomes of PLA patients. Methods: Consecutive adult patients with pathology addressed by PLA to the maxillary sinus were assessed. The primary outcome was the restoration of the lateral wall, and the secondary outcomes were early (< 90 days) and late morbidity (> 90 days). Results: Forty patients (52.8 ± 17 years, 62.5% female) were assessed. All patients had successful restoration of the lateral nasal wall (100% [95CI: 91.2%-100%]). The complications reported were primarily dysesthesia (early 10% and late 2.5%). Conclusion: The PLA provides robust access to the anterior, lateral, inferior, and inferomedial maxilla. PLA offers rapid mucosal recovery while preserving the normal physiology and the lacrimal systems with low morbidity.